Consciousness: Matter or EMF? - McFadden, Johnjoe (Frontiers in Human Neuroscience, 2023)
Conventional theories of consciousness (ToCs) that assume that the substrate of consciousness is the brain’s neuronal matter fail to account for fundamental features of consciousness, such as the binding problem. EM Field ToC’s propose that the substrate of consciousness is the brain’s best accounted by some kind of field in the brain. Electromagnetic (EM) ToCs propose that the conscious field is the brain’s well-known EM field. EM-ToCs were first proposed only around 20 years ago primarily to account for the experimental discovery that synchronous neuronal firing was the strongest neural correlate of consciousness (NCC). Although EM-ToCs are gaining increasing support, they remain controversial and are often ignored by neurobiologists and philosophers and passed over in most published reviews of consciousness. In this review I examine EM-ToCs against established criteria for distinguishing between ToCs and demonstrate that they outperform all conventional ToCs and provide novel insights into the nature of consciousness as well as a feasible route towards building artificial consciousnesses.